2022
DOI: 10.1099/mgen.0.000897
|View full text |Cite
|
Sign up to set email alerts
|

Increased phage resistance through lysogenic conversion accompanying emergence of monophasic Salmonella Typhimurium ST34 pandemic strain

Abstract: Salmonella enterica serovar Typhimurium (S. Typhimurium) comprises a group of closely related human and animal pathogens that account for a large proportion of all Salmonella infections globally. The epidemiological record of S. Typhimurium in Europe is characterized by successive waves of dominant clones, each prevailing for approximately 10–15 years before replacement. Succession o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…A prophage is an inherited form of a temperate bacteriophage, functioning as a dormant form of the viral genome, which is mostly integrated into the bacterial chromosome and replicates vertically with the genome of the bacterial host [ 28 , 29 ]. In bacterial cells, after infection with lysogenic phage, phenotypic changes (lysogenic conversion) are observed [ 28 , 30 ]. Lysogenic conversion may result in a resistance to related phages and in some cases, the acquisition of cargo genes affects population dynamics, including genes involved in virulence, metabolism, or antibiotic resistance genes [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prophage is an inherited form of a temperate bacteriophage, functioning as a dormant form of the viral genome, which is mostly integrated into the bacterial chromosome and replicates vertically with the genome of the bacterial host [ 28 , 29 ]. In bacterial cells, after infection with lysogenic phage, phenotypic changes (lysogenic conversion) are observed [ 28 , 30 ]. Lysogenic conversion may result in a resistance to related phages and in some cases, the acquisition of cargo genes affects population dynamics, including genes involved in virulence, metabolism, or antibiotic resistance genes [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In bacterial cells, after infection with lysogenic phage, phenotypic changes (lysogenic conversion) are observed [ 28 , 30 ]. Lysogenic conversion may result in a resistance to related phages and in some cases, the acquisition of cargo genes affects population dynamics, including genes involved in virulence, metabolism, or antibiotic resistance genes [ 30 ]. Until the lytic cycle resumes, no offspring are produced.…”
Section: Resultsmentioning
confidence: 99%
“…Owen et al, in 2021, identified BstA-phage-defense proteins encoded by prophage that inhibit exogenous lytic phage infections [77]. Similarly, Charity et al, in 2022, correlated mTmII prophage genome integration in Salmonella typhimurium to cause increased fitness and drug resistance [78]. Aforementioned studies are rather a glimpse at the ongoing research to unravel phage-host interactions and resistance mechanisms.…”
Section: Mary Et Al 2023mentioning
confidence: 99%